3D numerical investigation of the heat and flow transfer through cold protective clothing based on CFD. (August 2021) - Shen, Hua; An, Yuying; Zhang, Huimin; Wang, Fumei; He, Yu; Wang, Jilong; Tu, Lexi
Highlights: Heat and flow transfer through clothing under various ambient conditions. Combined effect of natural and forced convection in porous structure. Global relative importance of conduction, convection and radiation. Lowest comfort temperature at various activity levels for different clothing. Abstract: A three-dimensional (3D) model solving the heat and flow transfer through cold protective clothing under various ambient conditions was developed based on the torso thermal manikin in the present work. The conjugate problem of conduction, convection and radiation was simultaneously solved by the proposed model. The air in the computation domain was treated as a uniform turbulent flow, but it was considered as a slow air movement when the air was in the clothing modeled as a homogenous porous structure. Ideal contact between skin and clothing ensemble was assumed to eliminate the effect caused by the air layer enclosed at the gap. Validation study was performed by comparing the numerical results with experimental results obtained from the torso thermal manikin in a climate chamber. A good agreement was found with the maximum difference in heat flux and thermal resistance below 7.4% and 7.8%, respectively. The dependence of various parameters such as ambient temperature, air velocity and clothing thickness on clothing thermal insulation was further clarified by extensive parametric study. The local variations in temperature distribution, radiative and convective heat flux along the clothing outer surface were found to be significant, indicating that a space-average method would withhold the variation between different local positions. The global relative contribution of conduction, convection and radiation under different temperature and windy conditions were also evaluated. Besides, the lowest comfort temperature at activity level 2 met and 4 met was investigated for clothing with different thickness, and the effect exerted from wind was pronounced.